Analyzing Schizophrenic-prone text from social media content: a novel approach through ML and NLP - Rodela, Raisa Rahman; Efty, Farhan Tanvir; Rahman, Mubashira; Wajiha, Shaira (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2024.